Molnupiravir - the First Oral Antiviral for COVID-19: A Literature Review - Nur Afni; Suharjono Suharjono (Pharmacon: Jurnal Farmasi Indonesia, 2022)
The COVID-19 pandemic is still an unresolved global health concern, although half of the world's population has been vaccinated. The pharmaceutical industries are still struggling to develop effective antivirals against SARS-CoV-2. Molnupiravir is a new oral antiviral with antiviral properties by targeting coronavirus RNA. This literature review aims to describe the mechanism of action, efficacy, and safety of molnupiravir based on published preclinical and clinical studies for COVID-19 treatment. Relevant studies were collected by electronic databases, including Google Scholar, PubMed, and Science Direct. The inclusion criteria were preclinical and clinical trials related to molnupiravir as an antiviral for the COVID-19 treatment published in December 2019 to January 2022. Preclinical trials demonstrated therapeutic and prophylactic properties against SARS-CoV-2 in cell culture and animal models. Molnupiravir is currently under the emergency use authorization from the FDA to treat COVID-19. Its potent and broad antiviral activity is demonstrated through a mechanism of error catastrophe that causes coronavirus RNA mutagenesis. The published clinical trials have shown that molnupiravir is well-absorbed, well-tolerated, and has relatively mild side effects such as headache, nausea, and diarrhea with a minimal incidence at a dose of 800 mg twice daily. Time to viral RNA clearance was significantly decreased in patients administered molnupiravir 800 mg compared to those who administered placebo (14 days vs 15 days, P value=0,013). Molnupiravir is a promising oral antiviral that can reduce the incidence of COVID-19 hospitalization or death. Further clinical trials regarding its efficacy for severe symptoms and other clinical aspects such as drug interactions and contraindications are still needed.